2016
DOI: 10.1001/jamaophthalmol.2016.2906
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Marine ω-3 Fatty Acids and Incident Sight-Threatening Retinopathy in Middle-Aged and Older Individuals With Type 2 Diabetes

Abstract: IMPORTANCE Diabetic retinopathy (DR) is a devastating complication of individuals with type 2 diabetes mellitus. The retina is rich in long-chain ω-3 polyunsaturated fatty acids (LCω3PUFAs), which are substrate for oxylipins with anti-inflammatory and antiangiogenic properties. Experimental models support dietary LCω3PUFA protection against DR, but clinical data are lacking. OBJECTIVE To determine whether LCω3PUFA intake relates to a decreased incidence of sight-threatening DR in individuals with type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 24 publications
5
95
0
4
Order By: Relevance
“…The potential impact of compromised vitamin D, iron, and calcium levels on diabetes risk, diabetes management, and the development of diabetes comorbidities is not clear. However, adequate intake of the long-chain omega-3 fatty acids EPA and DHA has been associated with some benefits for patients with diabetes, including reduction of albuminuria, improvement in renal function, and risk reduction of diabetic retinopathy (4345). These fatty acids also have been associated with a lower risk of CVD incidence and mortality among patients with diabetes (46).…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of compromised vitamin D, iron, and calcium levels on diabetes risk, diabetes management, and the development of diabetes comorbidities is not clear. However, adequate intake of the long-chain omega-3 fatty acids EPA and DHA has been associated with some benefits for patients with diabetes, including reduction of albuminuria, improvement in renal function, and risk reduction of diabetic retinopathy (4345). These fatty acids also have been associated with a lower risk of CVD incidence and mortality among patients with diabetes (46).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the shift from omega-3 fatty acids to omega-6 fatty acids seen in diabetic dyslipidemia causes increased levels of bioactive lipids, which contributes to the pro-inflammatory environment seen in early stages of DR. A recent clinical trial (PREDIMED) demonstrated that dietary intake of long chain omega 3 fatty acids deceased the risk of DR in type 2 diabetic patients (81). One potential explanation for the beneficial effects of omega-3 fatty acids is the synthesis of resolvins.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…The leukotrienes, products of 5-lipoxygenase, play an important role in leukocyte recruitment and vascular permeability, and they are increased in the vitreous of diabetic patients 17,41 . Recently, a study showed that increased intake of long-chain -3 polyunsaturated fatty acids can decrease the progression of DR 42 , possibly by modulating the amount and type of eicosanoids made 43 .…”
Section: Inflammatory Mediators In Diabetic Retinopathymentioning
confidence: 99%